Juridical Analysis of the Occupational Safety and Health Management System in the Company - Marbun, Jaminuddin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Whatever we do almost all have risks if we are not careful about doing it. Some risks are small and some are large depending on the type of work to be performed. The threat of risk that will occur in this case is the risk of occupational safety and health that cannot be predicted when the event will occur which is clear that each worker must be careful to carry out their work. To overcome the risk of accidents and occupational health it is necessary to hold various efforts by the government, employers and workers to foster norms of protection for workers in accordance with industrial and technological advancements in the company. In order to anticipate workplace accidents in the company, one way is to implement an Occupational Safety and Health Management System that is united with the company's management so that employers can implement fully the protection of workers in employment relationships at the company.